Respostas
respondido por:
0
6-
x² - 100 = 0
x² = 100
x' = √100 = 10 e x'' = -√100 = -10
7-
x² - 7x = 0
x * (x - 7) = 0
x' = 0 e x'' - 7 = 0 ⇒ x'' = 7
8-
x² - 11x + 18 = 0
Δ = (-11)² - 4 * 1 * 18 = 121 - 72 = 49
x' = ( - (-11) + √49 ) / (2 * 1) = (11 + 7) / 2 = 18 / 2 = 9
x'' = ( - (-11) - √49 ) / (2 * 1) = (11 - 7) / 2 = 4 / 2 = 2
9-
-x² + 13x - 42 = 0
Δ = 13² - 4 * (-1) * (-42) = 169 - 168 = 1
x' = ( - 13 + √1 ) / (2 * (-1)) = (-13 + 1) / (-2) = (-12) / (-2) = 6
x'' = ( - 13 - √1 ) / (2 * (-1)) = (-13 - 1) / (-2) = (-14) / (-2) = 7
x² - 100 = 0
x² = 100
x' = √100 = 10 e x'' = -√100 = -10
7-
x² - 7x = 0
x * (x - 7) = 0
x' = 0 e x'' - 7 = 0 ⇒ x'' = 7
8-
x² - 11x + 18 = 0
Δ = (-11)² - 4 * 1 * 18 = 121 - 72 = 49
x' = ( - (-11) + √49 ) / (2 * 1) = (11 + 7) / 2 = 18 / 2 = 9
x'' = ( - (-11) - √49 ) / (2 * 1) = (11 - 7) / 2 = 4 / 2 = 2
9-
-x² + 13x - 42 = 0
Δ = 13² - 4 * (-1) * (-42) = 169 - 168 = 1
x' = ( - 13 + √1 ) / (2 * (-1)) = (-13 + 1) / (-2) = (-12) / (-2) = 6
x'' = ( - 13 - √1 ) / (2 * (-1)) = (-13 - 1) / (-2) = (-14) / (-2) = 7
respondido por:
0
6) x* - 100 = 0
x é igual à raiz quadrada de 100
x = 10
7) x* - 7x = 0
[delta] = - 7 . (- 7) - 4.1.0
[delta] = 49
x1 = - (- 7) + 7
....... —————
............. 2.1
x1 = 14/2 = 7
x2 = - (- 7) - 7
....... —————
............. 2.1
x2 = 0/2 = 0
8) x* - 11x + 18 = 0
[delta] = - 11 . (- 11) - 4.1.18
[delta] = 121 - 72
[delta] = 49
x1 = - (- 11) + 7 = 18/2 = 9
....... —————
............ 2.1
x2 = - (- 11) -7 = 4/2 = 2
....... —————
.............. 2.1
9) - x* + 13x - 42 = 0
[delta] = 13 . 13 - 4.(-1).(-42)
[delta] = 169 - 168
[delta] = 1
x1 = - 13 + 1 = -12/-2 = 6
...... ————
......... 2.(-1)
x2 = -13 - 1. = -14/-2 = 7
...... ————
........ 2.(-1)
Acho que deu pra entender. Meu teclado é bem limitado.
x é igual à raiz quadrada de 100
x = 10
7) x* - 7x = 0
[delta] = - 7 . (- 7) - 4.1.0
[delta] = 49
x1 = - (- 7) + 7
....... —————
............. 2.1
x1 = 14/2 = 7
x2 = - (- 7) - 7
....... —————
............. 2.1
x2 = 0/2 = 0
8) x* - 11x + 18 = 0
[delta] = - 11 . (- 11) - 4.1.18
[delta] = 121 - 72
[delta] = 49
x1 = - (- 11) + 7 = 18/2 = 9
....... —————
............ 2.1
x2 = - (- 11) -7 = 4/2 = 2
....... —————
.............. 2.1
9) - x* + 13x - 42 = 0
[delta] = 13 . 13 - 4.(-1).(-42)
[delta] = 169 - 168
[delta] = 1
x1 = - 13 + 1 = -12/-2 = 6
...... ————
......... 2.(-1)
x2 = -13 - 1. = -14/-2 = 7
...... ————
........ 2.(-1)
Acho que deu pra entender. Meu teclado é bem limitado.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás